2011
DOI: 10.1111/j.1526-4610.2011.01914.x
|View full text |Cite
|
Sign up to set email alerts
|

Headache Disorders in the Millennium Cohort: Epidemiology and Relations With Combat Deployment

Abstract: Objective.-Characterize migraine and other headache disorders within a large population-based US military cohort, with an emphasis on the temporal association between military deployment and exposure to combat.Background.-Little research has been published on the prevalence of headache disorders in the US military population, especially in relation to overseas deployments and exposure to combat. A higher than expected prevalence of migraine has previously been reported among deployed US soldiers in Iraq, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
31
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 30 publications
7
31
2
Order By: Relevance
“…While we observed a similar difference in prevalence of migraine by sex, the prevalence of migraine among both adult men and women in our study was higher than that reported in the U.S. population [21][22] or among servicemembers without limb loss [23]. Thus, while our findings mirror those in the general population with respect to sex differences, they indicate a potentially much higher overall burden of migraine for both men and women with traumatic limb loss, which may in part be because of the high prevalence of mental health conditions associated with increased risk of migraine [27][28]. Alternatively, self-report of migraine was not based on meeting any specific criteria, and if those reporting migraine included individuals with headaches that resembled but did not meet clinical criteria for true migraine, then the prevalence of migraine in our study closely resembles the combined prevalence of migraine and possible migraine in the survey by Theeler et al of recently deployed men and women [23].…”
Section: Discussioncontrasting
confidence: 49%
“…While we observed a similar difference in prevalence of migraine by sex, the prevalence of migraine among both adult men and women in our study was higher than that reported in the U.S. population [21][22] or among servicemembers without limb loss [23]. Thus, while our findings mirror those in the general population with respect to sex differences, they indicate a potentially much higher overall burden of migraine for both men and women with traumatic limb loss, which may in part be because of the high prevalence of mental health conditions associated with increased risk of migraine [27][28]. Alternatively, self-report of migraine was not based on meeting any specific criteria, and if those reporting migraine included individuals with headaches that resembled but did not meet clinical criteria for true migraine, then the prevalence of migraine in our study closely resembles the combined prevalence of migraine and possible migraine in the survey by Theeler et al of recently deployed men and women [23].…”
Section: Discussioncontrasting
confidence: 49%
“…Two recent studies have identified control groups for active duty deployed soldiers: civilians (Vargas, 2009) and military personnel who remain stateside (Jankosky et al, 2011). While descriptively informative, each of the control groups used in these studies may be problematic if unobservable factors correlated with active duty service are associated with physical and psychological health (Cesur et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…One recent study (Jankosky et al, 2011) has provided the first suggestive evidence that combat deployment may be associated with migraine headache. Using data from the Millennium Cohort Study, Jankosky et al (2011) compare migraine headache among those deployed to combat zones with migraine headache among non-deployers and find that deployment is associated with a substantial increase in the probability of a migraine diagnosis.…”
mentioning
confidence: 99%
“…One recent study (Jankosky et al, 2011) has provided the first suggestive evidence that combat deployment may be associated with migraine headache. Using data from the Millennium Cohort Study, Jankosky et al (2011) compare migraine headache among those deployed to combat zones with migraine headache among non-deployers and find that deployment is associated with a substantial increase in the probability of a migraine diagnosis. However, non-deployed Reservists or National Guardsmen and active-duty non-deployable soldiers may differ on many individual-level 7 unobservables related to health (Department of the Army AR 614-30, 2010;Cesur et al, 2011) or human capital (Hirsch and Mehay,2003), thus potentially contaminating estimates of the migraine effects of combat exposure.…”
mentioning
confidence: 99%